VD_FINDINFO Décision / 2013 / 608 vom 9. Juli 2013 - VD Tribunal cantonal (2013)
DÉTENTION PRÉVENTIVE, RISQUE DE FUITE, RISQUE DE COLLUSION | 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 221 CPP (CH)